2013
DOI: 10.1007/s10654-013-9834-7
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of prospective studies of coffee consumption and mortality for all causes, cancers and cardiovascular diseases

Abstract: Several prospective studies considered the relation between coffee consumption and mortality. Most studies, however, were underpowered to detect an association, since they included relatively few deaths. To obtain quantitative overall estimates, we combined all published data from prospective studies on the relation of coffee with mortality for all causes, all cancers, cardiovascular disease (CVD), coronary/ischemic heart disease (CHD/IHD) and stroke. A bibliography search, updated to January 2013, was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
2
17

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 76 publications
6
68
2
17
Order By: Relevance
“…As in many previous prospective cohort studies carried out among women [8,9,[23][24][25], coffee consumption was not associated with cancer mortality in our study, which is also in agreement with two recent meta-analyses [4,6]. Two prospective cohort studies in Japanese women reported some evidence for an inverse association between coffee consumption and cancer mortality [16,26].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As in many previous prospective cohort studies carried out among women [8,9,[23][24][25], coffee consumption was not associated with cancer mortality in our study, which is also in agreement with two recent meta-analyses [4,6]. Two prospective cohort studies in Japanese women reported some evidence for an inverse association between coffee consumption and cancer mortality [16,26].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in agreement with the results of the Nurses' Health Study and the National Institute of Health-AARP Diet and Health Study [9,14]. It is also consistent with three recent meta-analyses [4][5][6].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, a meta-analysis published in 2014 [28] concluded that moderate coffee consumption (3-5 cups/day) was associated with a lower CVD risk, and heavy coffee consumption (≥ 6 cups/day) was neither associated with a higher nor a lower risk of CVD. A further meta-analysis [29] has also showed that heavy coffee consumption was not associated with risk of CVD mortality. In contrast, the cohort study by Liu et al [30] found that 4 cups per day of coffee consumption was associated with increased mortality, but the association was only significant for participants under 55 years of age.…”
Section: Effects Of Coffee On the Cardiovascular Systemmentioning
confidence: 95%
“…Bei Patienten, die Kaffee trinken und gleichzeitig rauchen, war die Mortalität nicht reduziert [90]. In einer weiteren Studie konnte keine Reduktion der Gesamtmortalität durch Kaffee nachgewiesen werden, wäh-rend in einer kürzlich publizierten Metaanalyse die Gesamtmortalität reduziert war [91,92]. Im Stockholm Heart Epidemiology Program (SHEEP) bei Patienten nach einem akuten Myokardinfarkt sowie bei einer Subanalyse des Patientenkollektivs der Framingham Heart Study, in der ältere Patienten untersucht wurden, war der Kaffeekonsum mit einer geringeren kardiovaskulären Mortalität vergesellschaftet [93,94].…”
Section: Kaffee Und Kardiovaskuläre Erkrankungenunclassified